Local Health Departments and the Implementation of Evidence-Based Policies to Address Opioid Overdose Mortality. Issue 4 (October 2020) - Feuerstein-Simon, Rachel; Lowenstein, Margaret; Sharma, Meghana; Dupuis, Roxanne; Luna Marti, Xochitl; Cannuscio, Carolyn C.
Background: In the context of the opioid overdose crisis, local health departments are on the front lines, coordinating programs and services and translating state and federal policies into community action. While media reports describe growth of Overdose Education and Naloxone Distribution (OEND) programs among local health departments, little is known about program features, scope, and target populations. Methods: We surveyed health departments in 180 United States counties with high overdose mortality rates. Results: Among health officials from 54 counties (30% response), many counties reported implementation of evidence-based practices, with a high degree of programmatic variation. The majority of responding health departments (94%) conducted overdose education and naloxone distribution (OEND) programs. Programs were heterogeneous in scale, with a reported median of 250 naloxone kits (range 1–25, 000 kits) acquired for community distribution. In addition, four in five respondents were aware of their state's standing order policy for increasing naloxone access. While the majority of respondents reported county-level availability of at least one form of evidence-based medications to treat opioid use disorder (MOUD), many reported no availability of buprenorphine (33%) or methadone (43%). Conclusions: Local health departments are vital to reducing opioid overdose mortality, and many are implementing relevant evidence-based practices. To support further adoption of potentially life-saving strategies, health departments need adequate funding and staffing as well as policies and guidelines to support implementation.